Impact of an 18F-FDG PET/CT Radiotracer Injection Infiltration on Patient Management—A Case Report - Kiser, Jackson W.; Crowley, James R.; Wyatt, David A.; Lattanze, Ronald K. (Frontiers in Medicine, 2018)
Major management decisions in patients with solid tumors are often based on Flourine-18 radiolabeled fluorodeoxyglucose (FDG) PET/CT. The misadministration of FDG outside the systemic circulation can have an adverse impact on this test’s sensitivity1 and is not uncommon2 - 7. This report describes how an FDG misadministration led to a repeat PET/CT study, resulting in the visualization of distant metastases that changed the original treatment plan. The findings suggest that routine injection monitoring is indicated whenever sensitivity is critical, and support claims that infiltrations can confound interpretation of semi-quantitative PET outcome measures in patients who are followed longitudinally2.